2017
DOI: 10.1021/acs.energyfuels.7b01456
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Full-Sized Pore Structure and Fractal Characteristics of Marine–Continental Transitional Longtan Formation Shale of Sichuan Basin, South China

Abstract: Despite the recent significant progress reviewed in marine and continental shale gas reservoirs, there is no general investigation concerning marine−continental transitional shales, especially in the research of the pore structure and fractal characteristics of marine−continental shale reservoirs. In this study, the pore structure characteristics of 12 typical marine− continental transitional shale samples of the Upper Permian Longtan Formation collected from Southern Sichuan Basin were analyzed, combining tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 55 publications
2
56
0
Order By: Relevance
“…A larger fractal dimension indicates a complex pore structure and the strong heterogeneity of a reservoir (Zhang et al 2017;Tang et al 2019).…”
Section: Fractal Theorymentioning
confidence: 99%
“…A larger fractal dimension indicates a complex pore structure and the strong heterogeneity of a reservoir (Zhang et al 2017;Tang et al 2019).…”
Section: Fractal Theorymentioning
confidence: 99%
“…The pore structure of shales has strong heterogeneity, such as the PSD in the shale ranges from nanometer to micrometer scales; macropores, mesopores, and micropores have different contributions to the PV and SSA, respectively (Zhang J. et al, 2017;Zhang J. et al, 2019). The pore is the main place to adsorb and gather gas.…”
Section: Characterization Of the Full-sized Pore Structurementioning
confidence: 99%
“…Pore structure parameters, such as pore volume, special surface area, porosity, permeability, and pore size diameter, are available for the evaluation of natural gas reservoirs (Chalmers and Bustin, 2007;Ross and Bustin, 2009;Chalmers et al, 2012;Mastalerz et al, 2012;Zhang et al, 2017aZhang et al, , 2017b. For example, many previous studies suggested that the abundance of pores in shales is mainly controlled by the compositions of minerals and organic matter (Loucks et al, 2012;Ma et al, 2015;Xiong et al, 2015;Li Han et al, 2019).…”
Section: Analysis Of Influencing Factors Of Hydrocarbon Expulsion And...mentioning
confidence: 99%